Experimental and Natural Infections of Goats with Severe Fever with Thrombocytopenia Syndrome Virus: Evidence for Ticks as Viral Vector. - Yongjun Jiao; Xian Qi; Dapeng Liu; Xiaoyan Zeng; Yewu Han; Xiling Guo; Zhiyang Shi; Hua Wang; Minghao Zhou (Public Library of Science (PLoS), 2015)
BACKGROUND:Severe fever with thrombocytopenia syndrome virus (SFTSV), the causative agent for the fatal life-threatening infectious disease, severe fever with thrombocytopenia syndrome (SFTS), was first identified in the central and eastern regions of China. Although the viral RNA was detected in free-living and parasitic ticks, the vector for SFTSV remains unsettled. METHODOLOGY/PRINCIPAL FINDINGS:Firstly, an experimental infection study in goats was conducted in a bio-safety level-2 (BSL-2) facility to investigate virus transmission between animals. The results showed that infected animals did not shed virus to the outside through respiratory or digestive tract route, and the control animals did not get infected. Then, a natural infection study was carried out in the SFTSV endemic region. A cohort of naïve goats was used as sentinel animals in the study site. A variety of daily samples including goat sera, ticks and mosquitoes were collected for viral RNA and antibody (from serum only) detection, and virus isolation. We detected viral RNA from free-living and parasitic ticks rather than mosquitoes, and from goats after ticks' infestation. We also observed sero-conversion in all members of the animal cohort subsequently. The S segment sequences of the two recovered viral isolates from one infected goat and its parasitic ticks showed a 100% homology at the nucleic acid level. CONCLUSIONS/SIGNIFICANCE:In our natural infection study, close contact between goats does not appear to transmit SFTSV, however, the naïve animals were infected after ticks' infestation and two viral isolates derived from an infected goat and its parasitic ticks shared 100% of sequence identity. These data demonstrate that the etiologic agent for goat cohort's natural infection comes from environmental factors. Of these, ticks, especially the predominant species Haemaphysalis longicornis, probably act as vector for this pathogen. The findings in this study may help local health authorities formulate and focus preventive measures to contain this infection.